Assessing the validity of syntactic alternations as criterial features of proficiency in L2 writings in English - Mallart, Cyriel; Simpkin, Andrew; Ballier, Nicolas; Lissón, Paula; Venant, Rémi; Stearns, Bernardo; Li, Jen-Yu; Gaillat, Thomas (Research Methods in Applied Linguistics, 2025)
This article addresses Second Language (L2) writing development through an investigation of alternation-based metrics. We explore the paradigmatic production in learner English by linking language functions to specific grammatical paradigms. Using the EFCAMDAT as a gold standard and a corpus of French learners as an external test set, we employ a supervised learning framework to operationalize and evaluate seven alternations. We show that learner levels are associated with these seven alternations. Using ordinal regression Modeling for evaluation, the results show that all syntactic alternations are significant but yield a low impact if taken individually. However, their influence is shown to be impactful if taken as a group. These alternations and their measurement method suggest that it is possible to use them as part of broader-purpose Computer-Assisted Language Learning (CALL) systems focused on proficiency assessment. •This research explores seven syntactic alternation microsystems in L2 English, finding evidence of their relations with proficiency.•This research explores the use of probabilistic contextual methods to measure syntactic alternations.•Results show that the seven syntactic alternations are significant and explain 9.6% of the variation in CEFR proficiency.